2023
DOI: 10.3390/mi14051079
|View full text |Cite
|
Sign up to set email alerts
|

Study of Gas Film Characteristics in Electrochemical Discharge Machining and Their Effects on Discharge Energy Distribution

Abstract: Glass is a hard and brittle insulating material that is widely used in optics, biomedicine, and microelectromechanical systems. The electrochemical discharge process, which involves an effective microfabrication technology for insulating hard and brittle materials, can be used to perform effective microstructural processing on glass. The gas film is the most important medium in this process, and its quality is an important factor in the formation of good surface microstructures. This study focuses on the gas f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Geng et al [13] proposed a back ush electrochemical discharge machining technique to address recast layers and fractures, resulting in high-quality lm cooling holes. Geng et al [14] investigated the recast layer and elemental distribution after lm cooling hole machining using ECDM, while Liu et al [15] examined gas lm purity and consistent discharge energy distribution with ECDM. Vasudevan et al [16] and Zhang et al [17] addressed issues like thermal spalling, delamination, aking, splattering, recast layers, and cracking on ceramic coatings, proposing that ECDM can mitigate these problems.…”
Section: Introductionmentioning
confidence: 99%
“…Geng et al [13] proposed a back ush electrochemical discharge machining technique to address recast layers and fractures, resulting in high-quality lm cooling holes. Geng et al [14] investigated the recast layer and elemental distribution after lm cooling hole machining using ECDM, while Liu et al [15] examined gas lm purity and consistent discharge energy distribution with ECDM. Vasudevan et al [16] and Zhang et al [17] addressed issues like thermal spalling, delamination, aking, splattering, recast layers, and cracking on ceramic coatings, proposing that ECDM can mitigate these problems.…”
Section: Introductionmentioning
confidence: 99%
“…Liu, H. and Xieeryazidan, A. [18] investigated the effect of energy distribution on electrochemical discharge machining, and experiments showed that the optimal combination of process parameters at 50 V voltage, 20 kHz frequency, and 80% duty cycle achieved a more uniform distribution of discharge energy, which was able to efficiently machine pairs of hard and fragile materials. Chuang et al [19] utilized the interaction of electrochemical and EDM compensating techniques for the machining of CrNiFe alloy material machining; the machining accuracy was characterized by electrical pulse signal matching, processing time was reduced by 80%, and the efficiency of the equipment was improved.…”
Section: Introductionmentioning
confidence: 99%